Green and gold [videorecording (DVD)] - Nelson, Craig T.; Skelnar, Brandon; Walsh, M. Emmet, 1935-2024 (SDG Releasing, 2025)
A fourth-generation dairy farmer on the brink of losing his farm to the bank wagers everything on a bet with his beloved Green Bay Packers while his granddaughter pursues music to save what they've worked for their whole lives.